Benchmarking performances of L2 spoken Lithuanian produced by young learners - Juknevičienė, Rita (Taikomoji kalbotyra, 2022)
The Common European Framework of Reference (CEFR), widely recognized as one of the most important documents in foreign language teaching, defines the levels of communicative language proficiency. The common points of reference are primarily meant to assist foreign language teachers and test developers striving to adhere to a unified understanding of CEFR levels. Yet it is not uncommon among practitioners to claim a particular level of a task, text or sample of learner performance drawing merely on their individual experience and intuition, with only limited knowledge of the original descriptor scales. The main purpose of this paper is to describe general procedures for relating foreign language tests and learner performances to the CEFR as they are prescribed by the Association of Language Testers in Europe (ALTE). The five stages of the linking process are familiarisation, specification, standardisation training and benchmarking, standard setting and validation. While the full implementaion of the linking process is a complex undertaking mostly applied in the context of high stakes examinations, certain stages of the linking process could be implemented by individual language schools and programmes. Benchmarking is one of such stages. It involves identification of illustrative learner performances for different proficiency levels. This is a stage which also has its relevance in daily teaching practice and could be easily incorporated in routine assessment procedures thus increasing foreign language teachers’ awareness of CEFR levels. Therefore the discussion of the formal linking procedures in this paper is followed by a demonstration of an exercise in benchmarking. It is meant to acquaint the Lithuanian readers with the complexity of the linking process and encourage a more principled approach to level allocations. The exercise in alignment with CEFR level decribed here involves L2 spoken Lithuanian produced by five foreign learners of young age. Sample performances were taken from a corpus of L2 Lithuanian compiled within the XXX project. Since the subjects are children of 11–12 years, another important challenge in the alignment with the CEFR is children’s maturity and the necessary adaptation of CEFR descriptors for young learners. Qualitative analysis of five learner samples offers a number of insights into practicalities of linking procedures and discusses ways to ensure reliability and objectivity.